PENGARUH TERAPI LATIHAN MC KENZIE MENGURANGI KETERBATASAN GERAK THORACAL PADA PEKERJA BATIK DENGAN KELUHAN JOINT BLOCKADE THORACAL - Ade Irma Nahdliyyah; Dani Prastiwi (LPPM Universitas Pekalongan, 2015)
Joint blockade thoracal can occur as a result of excessive stretching or contraction and repeated that lasts a long time so that muscles experience spasms that eventually cause pain resulting in limitation of thoracal movement. One effort that can be done to improve the in limitation of thoracal movement is through Mc. Kenzie Ecercise.This study aimed at investigating the effect of Mc. Kenzie Ecercise in increasing the functional activity of the batik craftsmen with Joint blockade thoracal. This research was a quasy- experimental design with one group pre-test and post-test. The study population was batik craftsmen in Sijambe Village, Wonokerto, Wiradesa, Pekalongan, amounting to 80 people. Samples were obtained by using purposive sampling so that the sample of 20 people. Test used paired sample t-test.The results showed that the significant difference before and after exercise Mc. Kenzie with p=0.000.Keyword : Mc. Kenzie, Excercise, Joint blocade thoracal